2019
DOI: 10.1103/physreve.100.032144
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the performance of quantum Otto heat engines

Abstract: To optimize the performance of a heat engine in finite-time cycle, it is important to understand the finite-time effect of thermodynamic processes. Previously, we have shown that extra work is needed to complete a quantum adiabatic process in finite time, and proved that the extra work follows a C/τ 2 scaling for long control time τ . There the oscillating part of the extra work is neglected due to the complex energy-level structure of the particular quantum system. However, such oscillation of the extra work … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 63 publications
1
31
0
Order By: Relevance
“…Similarly, harmonic quantum Otto engines reach the Curzon-Ahlborn efficiency in the quasistatic limit [8,9]. More recently, it was demonstrated that the efficiency of endoreversible Otto engines at maximal power depends on the equation of state, i.e., the nature of the working medium [10][11][12][13][14] and the specific implementation of the power stroke [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, harmonic quantum Otto engines reach the Curzon-Ahlborn efficiency in the quasistatic limit [8,9]. More recently, it was demonstrated that the efficiency of endoreversible Otto engines at maximal power depends on the equation of state, i.e., the nature of the working medium [10][11][12][13][14] and the specific implementation of the power stroke [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Since the last century, with the maturity of quantum theory and its related technologies, people started to pay attention to the performance of quantum heat engines working in micro-scale within the framework of quantum thermodynamics [ 4 , 5 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Series of the quantum effect, such as coherence, entanglement, quantum phase transition, etc., of the working substance or heat source have been studied to realize better heat engines [ 13 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. On the other hand, with the development of non-equilibrium thermodynamics [ 2 , 3 , 28 ], the optimization of actual heat engines under the framework of finite-time thermodynamics attracted a wide range of attention [ 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Otto cycle (see Fig. 1) has been widely studied due to its analytic tractability [12,[16][17][18][21][22][23][24][25][26][27]. It has been reported that the quantum Otto engine can also be used as a precise thermometer [28] and the Otto engine with the finite power and the quasi-static efficiency can be achieved by the shortcut-to-adiabaticity technique [16].…”
Section: Introductionmentioning
confidence: 99%